Retiro de aportes del sistema privado de pensiones y finanzas personales en padres de familia de la escuela profesional de contabilidad UNAP 2020-2022 - Acuy Nolorbe, Marcia Eloisa (2023)
The economic crisis as a result of the health pandemic experienced between 2020 and 2022, affected households around the world, implementing the states various public policies and within them, the authorization of the withdrawal of contributions from the private pension system to cover needs of families, an aspect that has not been studied in the local environment and that it is important to address, the main purpose of the research being to analyze the contribution of withdrawal of contributions in personal finances in parents of accounting university students of the University National Survey of the Peruvian Amazon 2020-2022, with a non-experimental design and a population of 85 individuals with a type of observational quantitative research, with a collection instrument of 20 items and 7 identifying questions with a statistical reliability of 0.887 in Cronbach's alpha. , identifying that the withdrawal of contributions from the private pension system contributed positively to personal finances in participating parents in aspects such as balancing income with expenses, covering mainly basic needs, a percentage to investments, in addition to the fact that it is perceived that its end it had a positive use in families, being the most representative item infrastructure and food and that the effectiveness of the public policy of withdrawal of funds in personal finances presents a positive perception for 62% of participants.